Pro ASP.NET 3.5 in C# 2008 - MacDonald, Matthew; Szpuszta, Mario (Apress : Imprint: Apress, 2007)
ASP.NET 3.5 is Microsoft's revolutionary ASP.NET technology. It is the principal standard for creating dynamic web pages on the Windows platform. Pro ASP.NET 3.5 in C# 2008 raises the bar for high-quality, practical advice on learning and deploying Microsoft's dynamic web solution. Seasoned .NET professionals Matthew MacDonald and Mario Szpuszta explain how you can get the most from this groundbreaking technology. They cover ASP.NET 3.5 as a whole, illustrating both the brand-new features and the functionality carried over from previous versions of ASP. This book will give you the knowledge you need to code real ASP.NET 3.5 applications in the best possible style.